PENGGUNAAN BIRTHBALL TERHADAP NYERI PERSALINAN KALA 1 - Ibrahim; Arum Dwi Anjani; Yollanda Dwi Santi; Adelia Despriyanti (Universitas Batam, 2022)
Labor pain is a physiological process in labor with different pain intensity in each individual and usually comes and goes. This non-pharmacological method tends to be easier and safer to give to mothers in labor, one of which is the use of birth balls. Most births are painful, intense and sometimes traumatizing. However, pain itself is a natural thing to happen, caused by psychological and physiological factors. The purpose of this article is to determine the effect of giving the birth ball method on the intensity of labor pain before and after being given treatment